Computer on - line to study the energy issue among collisions - Alizoti, Alion (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Physics and its education is experiencing many changes concerning reconstruction of knowledge to improve physical concepts and their teaching and learning. New technologies and organized learning are being widely recommended to support new methods in teaching and learning. New technologies are meant to satisfy the physical need for perfecting methodologies and precision measurements meanwhile organized learning is aiming the implementation of efficient schemata in physics education. Therefore, organized learning with computer technologies is implemented to study mechanical collisions. The Computer – Interface – Sensor is used to verify the energy and momentum conservations in several cases of collisions. Class activies have enabled students to establish a good relationship between experimental quantities and theoretical qualities of collision energy and momentum.